Linguatula serrata (Porocephalida: Linguatulidae) Infection among Client-Owned Dogs in Jalingo, North Eastern Nigeria: Prevalence and Public Health Implications - Oseni Saheed Oluwasina; Onyiche Emmanuel ThankGod; Omonuwa Omojefe Augustine; Fufa Ido Gimba (Journal of Parasitology Research)
Pentastomiasis is a parasitic zoonosis endemic to western and central Africa. This study was undertaken to determine the prevalence and public health implications of Linguatulosis in client-owned dogs in Jalingo, North Eastern Nigeria. Seven hundred and seventy seven (777) dogs brought for treatment at the hospital were subjected to buccal (sublingual) examination for pentastomiasis. Parameters such as age, sex, and breeds were determined. Also, the months of the year were taken into consideration. An overall prevalence of 37.45% was recorded. Of the 477 dogs examined in 2010, 184 were positive representing prevalence of 38.57% and in 2011 107 were positive representing prevalence of 35.67%. The infection was higher in the male than in the female which does not differ significantly (P>0.05). There was no significant difference between sexes (P>0.05). However, significant difference (P<0.05) was observed between breeds and age of dogs examined. Season did not have much influence on the prevalence of Linguatulosis. The high prevalence of Linguatulosis in dogs and other animals found in this study highlights the need of improving preventative measures to reduce the rate of infection, which may pose a hazard to human health.